Aplikasi Sistem Pakar Rekomendasi Makanan untuk Memenuhi Kecukupan Gizi - William William; Kartika Gunadi; Anita Nathania Purbowo (Jurnal Infra, 2022)
Nutrition problems are one of the common problems in Indonesia. The lack of knowledge about nutritional needs is one of the main causes of nutritional problems. To avoid nutrition problems, everyone needs to know their daily calorie needs so they don’t eat more or less food than the required calories. Eating more than the required calories can lead to obesity while eating less than the required calories can lead to malnutrition. This research was made to help reduce nutrition problems by creating an application that can help users to know their daily calorie needs and provide food recommendations that suit their caloric needs. By using the forward chaining method to collect personal data from user and the genetic algorithm method to filter food to be recommended.Based on the results of the program test conducted, the genetic algorithm method used was successful in filtering food and recommending it where the total calories from the recommended foods are close to the users total calorie needs although not perfect and sometime still exceed the calories needed but not in large amounts. The list of food menus used as a reference is a balanced diet according to Ministry of Health, but further researchers can use other references.